Biological Denitrification of Nitrate Contaminated Ground Water with Elementary Sulfur - Gorathoki, Madan; Amatya, Iswar Man (Journal of Advanced College of Engineering and Management, 2019)
Extensive utilization of synthetic fertilizer and release of improperly treated wastewater from industrial or municipal facilities are the causes of nitrate contamination in natural water systems. Nitrate is one of the main contributors to eutrophication of surface water bodies which can cause severe ecological and environmental problems. Consumption of nitrates can have several detrimental health effects. One adverse health effect is methemoglobinemia or “blue-baby" syndrome. Sulfur based biological denitrification process is autotrophic denitrification using Thiobacillus denitriflcans, in which process is conducted by denitrifying bacteria which require inorganic carbon for carbon source. These denitrifying bacteria oxidizes elemental sulfur to sulphate while reducing nitrate to nitrogen gas, thereby eliminating the need for addition of organic carbon compounds as energy sources to drive denitrification. This Study was conducted on biological denitrification with elemental sulfur packed small-scale bed columns and it was found to be maximum 39 percent efficiency of NO3-N removal at 1.5 hours HRT having bicarbonate range 153.72 to 207.40 mg/l and that of TIN removal was up to 35 percent removal efficiency. In this biological process, elemental sulfur is converted into sulfate, and this renders the method unsuitable for the treatment of ground water containing high levels of endogenous sulfate.